Farmers’ Perception of Integrated Pest Management and its Impact on Cucumber Production in Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
IPM is an ecosystem-based strategy that focuses on long-term prevention of pests or their damage through a combination of techniques such as biological control, habitat manipulation, modification of cultural practices, and use of resistant varieties. Farmers’ perception of integrated pest management (IPM) and its impact on cucumber (Cucumis sativus L.) production were assessed in Bangladesh using few econometric models. A total of 119 cucumber farmers were interviewed in 2015 to achieve the objectives. Most of farmers perceived that IPM was beneficial for farmers’ health, water bodies. IPM adoption significantly reduced the pesticide applications cost per hectare (P